2019
DOI: 10.3390/nu11020357
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Potential of Egg Consumption and Egg Bioactive Components on Type-2 Diabetes

Abstract: Type-2 diabetes (T2D) is one of the major global health challenges and a substantial economic burden. Egg and egg-derived components have been indicated to possess antioxidant, anti-inflammatory, anti-hypertensive, immunomodulatory, and anti-cancer activities. However, the scientific evidence about the benefits of egg on T2D is debatable. The relationship between egg consumption and the risk of T2D from observational epidemiological studies is not consistent. Interventional clinical studies, however, provide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 136 publications
(168 reference statements)
0
19
0
2
Order By: Relevance
“…In the US population, eggs are often consumed with red or processed meat, refined grains, and sugary beverages. Therefore, heterogeneity in the response may be attributable to dietary patterns [4,105]. The same trend was observed in Korean T2DM patients, and higher egg consumption increased the risk for CVD, thus providing a basis for the development of an optimal dietary cholesterol intake guideline for the Korean population [109].…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 82%
See 2 more Smart Citations
“…In the US population, eggs are often consumed with red or processed meat, refined grains, and sugary beverages. Therefore, heterogeneity in the response may be attributable to dietary patterns [4,105]. The same trend was observed in Korean T2DM patients, and higher egg consumption increased the risk for CVD, thus providing a basis for the development of an optimal dietary cholesterol intake guideline for the Korean population [109].…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 82%
“…In observation studies reported from several countries, no association is observed between egg consumption and T2DM in healthy persons or no hazardous in T2DM patients [3,4,9,[97][98][99][100][101]. In some cases, egg consumption lowers the risk of T2DM or ameliorates glycemic control [96,[102][103][104][105][106][107]. In contrast, several studies indicate a positive association between egg consumption and T2DM risk [92,98,[108][109][110].…”
Section: Egg and Type 2 Diabetes Mellitusmentioning
confidence: 95%
See 1 more Smart Citation
“…These conflicting findings may be caused by differences in dietary patterns and socioeconomic factors. Another explanation could be that eggs may also offer some protective effect against diabetes: egg white hydrolysate, lutein, zeaxanthin, and angiotensin I-converting enzyme inhibitory tripeptides from eggs have been shown to protect against glucose and insulin resistance, oxidative stress, and inflammation in the context of type 2 diabetes (53).…”
Section: Discussionmentioning
confidence: 99%
“…117,118 The debate on the role of eggs for CVD prevention would remain largely as the increases of total and LDL cholesterol levels undoubtedly translate into either neutral or harmful CVD outcomes in different clinical trials and metanalyses. [119][120][121][122] It must be acknowledged that SFA are diverse compounds with variable effects on CHD risk depending on many factors apart from the dietary SFA intake, such as the SFA status, biomarkers and the carbon length of the SFA. 123 Genetic factors contribute to the risk of CHD related to the dietary intake of C-18 fatty acid.…”
Section: Eggsmentioning
confidence: 99%